Experimentally determined temperature thresholds for Arctic plankton community metabolism - Holding, Johnna; Duarte, Carlos M.; Arrieta, Jesús M.; Vaquer-Suyner3, Riser; Coello-Camba, Alexandra; Wassmann, Paul; Agusti, Susana (Biogeosciences, 2013)
Climate warming is especially severe in the Arctic, where the average temperature is increasing 0.4 C per decade, two to three times higher than the global average rate. Furthermore, the Arctic has lost more than half of its summer ice extent since 1980 and predictions suggest that the Arctic will be ice free in the summer as early as 2050, which could increase the rate of warming. Predictions based on the metabolic theory of ecology assume that temperature increase will enhance metabolic rates and thus both the rate of primary production and respiration will increase. However, these predictions do not consider the specific metabolic balance of the communities. We tested, experimentally, the response of Arctic plankton communities to seawater temperature spanning from 1 C to 10 C. Two types of communities were tested, open-ocean Arctic communities from water collected in the Barents Sea and Atlantic influenced fjord communities from water collected in the Svalbard fjord system. Metabolic rates did indeed increase as suggested by metabolic theory, however these results suggest an experimental temperature threshold of 5 C, beyond which the metabolism of plankton communities shifts from autotrophic to heterotrophic. This threshold is also validated by field measurements across a range of temperatures which suggested a temperature 5.4 C beyond which Arctic plankton communities switch to heterotrophy. Barents Sea communities showed a much clearer threshold response to temperature manipulations than fjord communities.